Rapid assessment of the distribution of myxomycetes in a southwestern Amazon forest - Rojas Alvarado, Carlos Alonso (2012)
The distribution of fruit bodies of myxomycetes under different ecological conditions at the Los Amigos Biological Station in southeastern Peru was studied. Six study areas were surveyed using a combined field-laboratory methodology under different climatic conditions. Sixty species were recorded and differences in fruit body abundance and structure of the assemblages were found among collecting periods. A diversity analysis based on fruit bodies showed that values were predominantly higher during the dry period. An analysis of microenvironmental conditions applied to a subset of data collected in the field showed that pH and substratum diameter accounted for most of the variation. In addition, the most abundant myxomycetes based on fruit body occurrence showed a multivariate arrangement that suggests the existence of functional groups.